Insecticidal properties of Gymnema sylvestre R.Br. against the storage pest, Tribolium castaneum Herbst - Ahalya, S.; Mikunthan, G. (Medicinal Plants - International Journal of Phytomedicines and Related Industries., 2011)
Insecticidal activity of many plants against several insect pests has been demonstrated. In this regard, an attempt has been made to analyze the insecticidal effects of the medicinal herb, Gymnema sylvestre on a storage pest, Tribolium castaneum. G. sylvestre leaves were used to prepare different extracts. Prepared seven different formulations were studied for their effect on mortality and progeny production against insect pest T. castaneum. Adults of T. castaneum were exposed to the treated broken rice and the mortality was assessed after 24h, 72h, 7days, 14days and 21 days of exposure. Progeny count of T. castaneum was done at the same mentioned intervals. Separately ethanolic extract was assessed for mortality by residual film assay and the mortality was assessed after 24h and 48h of exposure. Exposed T. castaneum showed significant mortality in all formulations. Observed mortality percentage increased with increase in time intervals after application but the extract concentrations had no significant effect. Cumulative mortality (52.2%) and progeny suppression (82.4%) were higher in leaf powder paste. The mortality in ethanolic extract was 100% at 24h at 300mg dosage. LD50 value was found as 17.5mg and 5mg for 24h and 48h, respectively
Keywords: Gymnema Sylvestre; Progeny Production; Mortality; Tribolium castaneum; Extracts